Response of Bacterial Metabolic Activity to the River Discharge in the Pearl River Estuary: Implication for CO2 Degassing Fluxes - Li, Xiangfu; Xu, Jie; Shi, Zhen; Li, Ruihuan (Frontiers in Microbiology, 2019)
Bacterial production (BP), respiration (BR) and growth efficiency (BGE) were simultaneously determined along an environmental gradient in the Pearl River Estuary (PRE) in the wet season (May 2015) and the dry season (January 2016), in order to examine bacterial responses to the riverine dissolved organic carbon (DOC) in the PRE. The Pearl River discharge delivered labile dissolved organic matters (DOM) with low DOC:DON ratio, resulting in a clear gradient in DOC concentrations and DOC:DON ratios. BP (3.93–144 μg C L−1 d−1) was more variable than BR (64.6–567 μg C L−1 d−1) in terms of the percentage, along an environmental gradient in the PRE. In response to riverine DOC input, BP and the cell-specific BP increased; in contrast, the cell-specific bacterial respiration declined, likely because labile riverine DOC mitigated energetic cost for cell maintenance. Consequently, an increase in bacterial respiration was less than expected. Our findings implied that the input of highly bioavailable riverine DOC altered the carbon portioning between anabolic and catabolic pathways, consequently decreasing the fraction of DOC that bacterioplankton utilized for bacterial respiration. This might be one of the underlying mechanisms for the low CO2 degassing in the PRE receiving large amounts of sewage DOC.